2002
DOI: 10.1007/s10158-002-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic leg motoneurons in the isolated CNS of adult Manduca produce patterned activity in response to pilocarpine, which is distinct from that produced in larvae

Abstract: In the hawkmoth, Manduca sexta, thoracic leg motoneurons survive the degeneration of the larval leg muscles to innervate new muscles of the adult legs. The same motoneurons, therefore, participate in the very different modes of terrestrial locomotion that are used by larvae (crawling) and adults (walking). Consequently, changes in locomotor behavior may reflect changes in both the CNS and periphery. The present study was undertaken to determine whether motor patterns produced by the isolated CNS of adult Mandu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…In contrast, in legged locomotion, where properties of the substrate with which the legs interact can drastically change, local information about current leg states plays an essential role in coordinating the limbs (Cattaert and Le Ray, 2001;Pearson, 2004;Ritzmann and Büschges, 2007;Borgmann et al, 2007;Borgmann et al, 2009). An important context-specific role for sensory feedback was also suggested by Johnston and Levine (Johnston and Levine, 2002), following their detailed analysis of differences between patterned motor activities evoked from isolated larvae or adult central nervous systems in Manduca, and activity patterns observed in the intact animals.…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, in legged locomotion, where properties of the substrate with which the legs interact can drastically change, local information about current leg states plays an essential role in coordinating the limbs (Cattaert and Le Ray, 2001;Pearson, 2004;Ritzmann and Büschges, 2007;Borgmann et al, 2007;Borgmann et al, 2009). An important context-specific role for sensory feedback was also suggested by Johnston and Levine (Johnston and Levine, 2002), following their detailed analysis of differences between patterned motor activities evoked from isolated larvae or adult central nervous systems in Manduca, and activity patterns observed in the intact animals.…”
Section: Introductionmentioning
confidence: 86%
“…In contrast, there is evidence confirming the importance of central inter-segmental neural pathways for the coordination of local networks controlling leg movements in insect walking, for example. This has been shown for the cockroach P. americana (Pearson and Iles, 1973), the locust Schistocerca americana (Ryckebusch and Laurent, 1993) and the hawk moth Manduca sexta (Johnston and Levine, 2002). However, studies have shown the role of local sensory feedback in establishing inter-leg coordination, e.g.…”
Section: Introductionmentioning
confidence: 87%
“…However, studies have shown the role of local sensory feedback in establishing inter-leg coordination, e.g. in the hawk moth (Johnston and Levine, 1996;Johnston and Levine, 2002) and the stick insect C. morosus (Borgmann et al, 2009;Büschges et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The right scheme depicts the situation, in which rhythmic activity that is largely coupled to the forward stepping front leg is generated in the metathoracic segment, when one front and one middle leg are present ). Also in this situation, all other legs just generate an increase in tonic activity in the thorax-coxa motoneurons and especially contralateral influences are very weak also known to play important roles in a variety of other legged animals like cat (Akay et al 2006), crayfish (Cruse and Müller 1986;Cattaert and LeRay 2001), turtle (Samara and Currie (2007), human (Haridas and Zehr 2003), and in some cases can overrule central commands (Johnston and Levine 2002). In the case of undulated crawling and swimming, electrophysiological and modeling studies showed that central coupling among the segmental CPGs is primarily responsible for inter-segmental coordination.…”
Section: Inter-segmental Coordinationmentioning
confidence: 97%